(untitled) (Bangladesh Journal of Library and Information Science, 2012)
The digital revolution throughout the world has brought about new challenges as well as new opportunities for the information professionals. The information professionals of the developing countries are grappling with problems like weak infrastructure, lack of skilled manpower, financial stringency etc. in implementing information and communication technologies in the libraries and also in the digitization of information resources. This paper explores the problems and potential of ICT and digitization in context of the library and information sector of Bangladesh. An elaborate analysis of various challenges for establishing digital information systems and services in the backdrop of the socio-economic realities of Bangladesh has been presented in the paper, along with indications as to how these challenges could be overcome. The paper ends with the conviction that, if these challenges could be dealt with successfully, the Vision 2021 stated by the Government could be realized in time. Bangladesh Journal of Library and Information Science Vol.2(1) July 2012 pp.57-66 DOI: http://dx.doi.org/10.3329/bjlis.v2i1.12922